Pelatihan Teknik Pengelasan dan Pengecatan Atomozing Bagi Santri Pesantren Anak Yatim Darul Hikmah Cot Yang-Kuta Baro Aceh Besar - Akhyar; Sary, Ratna; Husaini; Khairil; Edhy, Sarwo; Tamlicha, Akram; Hasanuddin, Iskandar; Zulfan; Farhan, Ahmad (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2024)
Islamic boarding schools are traditional educational institutions that prioritize a religion-based curriculum. The Darul Hikmah Orphans Islamic Boarding School, located in Cot Yang Village, Kuta Barou District, Aceh Besar Regency, Aceh Province, faces the challenge of low levels of entrepreneurial skills in the field of welding and atomizing painting due to the absence of this material in their curriculum. To overcome this, atomizing welding and painting training was carried out at Islamic boarding schools, which aimed to improve students' hard skills in this field. This training is also planned to develop business units, including the establishment of atomizing welding and painting workshops. This atomizing welding and painting entrepreneurship training program is measured by several parameters, with the output being the basic welding technical skills obtained by the students. It is hoped that this program will produce entrepreneurs in atomizing welding and painting workshops that will benefit the environment of the Darul Hikmah Cot Yang Orphan Islamic Boarding School. The training implementation stages include welding and painting theory, occupational health and safety (K3), as well as practice and assistance in basic welding and painting, with the final product being a table. The training material was adopted from teaching welding and painting practices at Syiah Kuala Darussalam University-Aceh. The result of this training is an increase in participants' knowledge in welding and painting, as well as their ability to apply these processes by prioritizing K3 (Occupational Safety and Health).